Analisis Hasil Pengukuran Tegangan Permukaan Menggunakan Metode Cookbook terhadap Suhu dan Panjang Tali - Hanifah, Rifda Arifa; Heryawan, Muhammad Agum; Insani, Salwa Mulya; Malik, Adam (Universitas Garut, 2026)
This study aims to evaluate the feasibility of a cookbook-based practicum method as an experimental technique in physics learning, particularly for the concept of liquid surface tension, and to examine its limitations related to the effects of temperature and rope length. The experiment was conducted at the Integrated Laboratory of UIN Sunan Gunung Djati Bandung using simple materials such as soapy water, yarn, chopsticks, and a thermometer. This study examines the relationship between temperature and surface tension, which is theoretically inversely proportional. However, the experimental results show that surface tension increases with increasing temperature, indicating a direct relationship. This discrepancy between experimental results and theory occurs due to a decrease in liquid temperature during the practicum process, where the initial temperature of the hot water at 72°C decreased to near room temperature (22°C) by the end of the experiment, thereby affecting the measured surface tension values. The study also shows that variations in rope length affect the radius and surface tension of the liquid, indicating a shift in the distribution of intermolecular forces at the surface. The implications of these findings highlight the importance of monitoring experimental conditions and the need for a laboratory approach that is both more accurate and practical for educational purposes. These findings further emphasize that the cookbook-based practicum method is effective in supporting qualitative understanding of surface tension concepts, but has limitations in quantitative accuracy. Therefore, this study encourages the development of more structured and controlled simple practicum guidelines to support physics learning in educational laboratories.